MakerArcade: Using Gaming and Physical Computing for Playful Making, Learning, and Creativity - Seyed, Teddy; Halleux, Jonathan "Peli" de; Moskal, Michal; Devine, James; Finney, Joe; Hodges, Steve; Ball, Thomas (CHI 2019 Extended Abstracts, 2019)
The growing maker movement has created a number of hardware and construction toolkits that lower the barriers of entry into programming for youth and others, using a variety of approaches, such as gaming or robotics. For constructionist-like kits that use gaming, many are focused on designing and programming games that are single player, and few explore using physical and craft-like approaches that move beyond the screen and single player experiences. Moving beyond the screen to incorporate physical sensors into the creation of gaming experiences provides new opportunities for learning about concepts in a variety of areas in computer science and making. In this early work, we elucidate our design goals and prototype for a mini-arcade system that builds upon principles in constructionist gaming – making games to learn programming – as well as physical computing.